Pengaruh Service Quality Dan Store Image Terhadap Customer Satisfaction (studi pada Karyawan di PT Midi Utama Indonesia Tbk) - Siti Fauziah (Journal of Economic, Management and Entrepreneurship, 2023)
This research is to determine the significant influence of service quality on customer satisfaction, to determine the significant influence of store image on customer satisfaction and to determine the significant influence of service quality on customer satisfaction. The type of research in this study uses a descriptive quantitative approach. The data used is primary data sources. Data analysis in this research uses multiple linear regression analysis. Based on the results of the hypothesis test from the F test, the calculated F value is greater than the F table, it can be concluded that there is a significant influence between service quality (X1), store image (X2) simultaneously on customer satisfaction (Y). Sig value. in the table above is 0.000, which is smaller than the significance level used (0.05), so it can be concluded that there is a significant influence between service quality (X1), store image (X2) simultaneously on customer satisfaction (Y). The R value is 0.857, so it can be seen that the R Square value is 0.734, meaning that the ability of the independent variable to explain the variance of the dependent variable is 73.4%, meaning there is 26.6% of the variance in the dependent variable which is explained by other factors